A Study on the Criteria for Branding Contractor Construction Sector Companies in Turkey - Cako, Seher; Cinar, Candan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2012)
Today, corporate brand is also important for companies that participate in the construction industry as with all companies. Corporate culture of construction companies, marketing and contact points of view, characteristics of products or services, provide the required quality standards, out of the institution professional services, to follow the technology and research and development work are very important to create institution's brand value. In this study, contractor in the construction sector in Turkey how they understand the brand value and fulfill the conditions necessary to reveal the brand value creation processes and how well they fulfill them was investigated. For this reason the criterias which are company structure, brand positioning, brand communication, product, marketing & sales and innovation in technology have been evaluated in a survey to understand to follow up the contractor companies in the construction sector in Turkey. Branding and market positioning depend on fullfillment of certain conditions and criterias. It has been realised that corporate culture of companies, quality of the product, professional services, marketing and communications perspectives constitute an important process to increase the perceived value of a product or a company in the market.
Keywords: Brand; brand value; branding criteria; building contractor; Architecture